The color of family a novel - Jones, Patricia (Avon Trade, 2004)
Raising her own two children in Baltimore, Antonia Racine, a proud, strong African-American wife and mother, hides a long-time secret about Clayton Cannon, a concert pianist who has grown up in a privileged white family, until she decides that it is time to reveal that Clayton is the result of a clandestine love affair between her late brother and a white woman in the segregated South.
Keywords: aRacially mixed people -- vFiction; aPassing (Identity) -- vFiction; aBrothers -- xDeath -- vFiction; aBirthfathers -- vFiction; aPianists -- vFiction; aNephews -- vFiction; aTwins -- vFiction; aNew Orleans (La.) -- vFiction; aPsychological fiction; aDomestic fiction; Domestic fiction; Psychological fiction